Solution of equations1 and 2





In this page solution of equations1 and 2 we are going to see solution for first and second questions.

Question 1:

Solve the equation 7 (x - 3) + 2 (2x - 5) - 3(x - 5) = 8

Solution:


           7 (x - 3) + 2 (2x - 5) - 3(x - 5) = 8

           7 x - 21 + 4 x - 10 - 3 x + 15 = 8

           7 x + 4 x - 3 x - 21 - 10 + 15 = 8

            11 x - 3 x - 31 + 15 = 8

                     8 x - 16 = 8

                            8 x = 8 + 16

                            8 x = 24

                               x = 24/8

                               x = 3

Checking:

 7 (x - 3) + 2 (2x - 5) - 3(x - 5) = 8

 7 (3 - 3) + 2 (2(3) - 5) - 3 (3 - 5) = 8

  7 (0) + 2 (6 - 5 ) - 3(-2) = 8

       0 + 2 (1) + 6 = 8

                 2 + 6 = 8

                      8 = 8


Solutions of Equations1 and 2


Question 2:

Solve the equation 4 x - (2 + 4x) - 2 (x - 1) = -8 (x -3)

Solution:


           4 x - (2 + 4x) - 2 (x - 1) = -8 (x -3)

           4 x - 2 - 4 x - 2 x + 2 = - 8 x + 24

           4 x - 4 x - 2 x - 2 + 2 = - 8 x + 24

                                  - 2 x = - 8 x + 24

                          - 2 x + 8 x = 24 

                                    6 x = 24

                                      x = 24 /6

                                      x = 4

We will check the answer by substituting the value of x in the given equation.

Checking:


 4 x - (2 + 4x) - 2 (x - 1) = -8 (x -3)

 4 (4) -  (2 + 4(4))  - 2 (4 - 1) = -8 ( 4 -3)

 16 -  (2 + 16) - 2 (3) = - 8(1)

  16 - 18 - 6 = - 8

       16 - 24 = - 8

          -8 = - 8

            8 = 8                   

HTML Comment Box is loading comments...






equations1 and 2 to Worksheet